MENGEMBANGKAN KARAKTER JIWA KEWIRAUSAHAAN PESERTA DIDIK SMK NEGERI 1 PENUKAL MELALUI PROGRAM MARKET DAY - Jon Areli, Ahmad (Graduate Program Magister Manajemen Pendidikan, 2018)
This study aimed at 1) determining the implementation of the program maket day which is one of the schools flagship program, 2) knowing the role of market day program in developing the entrepreneurship character of learners SMK Negeri 1 Penukal Kab. Pali. The ability of learners to be developed not only academic aspects but also non academic. This research was a descriptive qualitative using phenomenolgy approach, data source obtained through interview, observation, and documentation. Data were analyzed inductively, the exposure of the research result was descriptive. From the research results obtained that the implementation of Market Day program implemented by the school runs regularly every Friday and related to the building a positive culture for the citizens of the school. Students finally recognize and understand and familiar with trading activities and eventually grow in the students of the character of an entrepreneur is responsible, risk-taking, independent, hard work, communicative and can carry out financial management.